Pengembangan Konsep Model Supervisi Pembelajaran sebagai Upaya Peningkatan Profesionalisme Guru dalam Pengendalian Mutu Pendidikan - Mashari, Ali; Prabowo, Sugeng Listyo (Tapis: Jurnal Penelitian Ilmiah, 2023)
The current implementation of learning supervision tends to focus on just one supervision technique, namely supervision of class visits, which indicates that there is no opportunity for a supervisor to introduce innovations about learning to teachers. The tendency for the implementation of educational supervision to be carried out by supervisors who lack professionalism in their current work is also based more on the relationship between superiors and subordinates. The condition of this relationship does not foster a partnership between the supervisor and the party being supervised. The research uses R & D research, and aims to produce a Learning Evaluation Model product as an effort to increase teacher professionalism in controlling the quality of education in Lampung Province. Research data collection techniques were carried out through interviews, observation and documentation. the research steps are: 1) preliminary research, 2) theoretical studies, 3) product/prototype design, 4) expert validation, 5) model revision; After receiving input from the rater, the researcher revised the prototype; 6) Limited Group Test, 7) Model Revision, 8) Large Group Test. The results of the study show that the real conditions in the implementation of learning supervision in increasing teacher professionalism for controlling the quality of education are still not optimal, especially in mentoring and coaching by school principals so that there are still many obstacles both internally and externally. The results of the study also show that the development of the concept of learning supervision models in increasing teacher professionalism is very necessary in order to control the quality of education so that it continues to be better. Based on the results of the research findings and discussion, there are many weaknesses in the implementation of learning supervision in increasing teacher professionalism and by taking into account all the facts and phenomena that develop in the field, the authors propose a model of learning supervision in increasing teacher professionalism which is a systematic hypothetical.